Newly Discovered Natural Hosts of Tomato chlorosis virus in Costa Rica - Barboza Vargas, Natalia María (2011)
Tomato chlorosis virus (ToCV) is an emerging whitefly-transmitted crinivirus. In Costa Rica in 2007, ToCV was detected in field-grown and greenhouse tomato (Solanum lycopersicum L.) plants causing symptoms of severe yellowing and foliar chlorosis.